2018
DOI: 10.1182/blood-2018-02-831289
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic efficacy of pathogen-inactivated vs untreated platelets: a randomized controlled trial

Abstract: Pathogen inactivation of platelet concentrates reduces the risk for blood-borne infections. However, its effect on platelet function and hemostatic efficacy of transfusion is unclear. We conducted a randomized noninferiority trial comparing the efficacy of pathogen-inactivated platelets using riboflavin and UV B illumination technology (intervention) compared with standard plasma-stored platelets (control) for the prevention of bleeding in patients with hematologic malignancies and thrombocytopenia. The primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 28 publications
3
57
0
Order By: Relevance
“…This, however, may be explained by the fact that these only use fresh platelets ( 55 , 56 ), while pathogen reduction did not affect platelet internalization directly after treatment, but rather enhanced the storage-mediated internalization. Interestingly, two clinical trials were recently published that may confirm this hypothesis ( 57 , 58 ). Namely, one of these studies stored platelets on average for 1 day and showed a protective effect of pathogen inactivation ( 58 , 59 ), whereas the other trial stored platelets on average for 4 days and did not show any protective effect of pathogen inactivation ( 57 ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This, however, may be explained by the fact that these only use fresh platelets ( 55 , 56 ), while pathogen reduction did not affect platelet internalization directly after treatment, but rather enhanced the storage-mediated internalization. Interestingly, two clinical trials were recently published that may confirm this hypothesis ( 57 , 58 ). Namely, one of these studies stored platelets on average for 1 day and showed a protective effect of pathogen inactivation ( 58 , 59 ), whereas the other trial stored platelets on average for 4 days and did not show any protective effect of pathogen inactivation ( 57 ).…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, two clinical trials were recently published that may confirm this hypothesis ( 57 , 58 ). Namely, one of these studies stored platelets on average for 1 day and showed a protective effect of pathogen inactivation ( 58 , 59 ), whereas the other trial stored platelets on average for 4 days and did not show any protective effect of pathogen inactivation ( 57 ).…”
Section: Discussionmentioning
confidence: 92%
“…12 Concerns expressed regarding the use of PRPs include the potential need for maintaining a dual inventory of platelets due to supply limitations, decreased platelet count increments (PCIs), 13 risk of human leukocyte antigen (HLA) alloimmunization, 14 and the effect of psoralen on neonatal, pediatric, and obstetric patients. [15][16][17] Even with noninferior hemostatic function in hematology oncology patients, 18,19 decreased PCIs may result in increased platelet utilization and reduced platelet inventory. Increased HLA alloimmunization 14 may make finding suitable platelet products more difficult, an additional challenge for TSPs and clinicians.…”
Section: Pathogen Reduction (Pr)mentioning
confidence: 99%
“…The CCI at one and 24 h after transfusion is decreased in patients receiving PRT treated products, compared to patients receiving control products. In two recent clinical trials Grade 2 or higher bleeding was the primary endpoint [55,66].…”
Section: Clinical Performancementioning
confidence: 99%